Information Sharing and Financial Sector Development in Africa - Vanessa Tchamyou; Simplice Asongu (African Governance and Development Institute (AGDI), 2016)
This study investigates the effect information sharing has on financial sector development in 53 African countries for the period 2004-2011. Information sharing is measured with private credit bureaus and public credit registries. Hitherto unexplored dimensions of financial sector development are employed, namely: financial sector dynamics of formalization, informalization and non-formalization. The empirical evidence is based on Ordinary Least Squares (OLS) and Generalised Method of Moments (GMM). The following findings are established. Information sharing bureaus increase (reduce) formal (informal/non-formal) financial sector development. In order to ensure that information sharing bureaus improve (decrease) formal (informal/non-formal) financial development, public credit registries should have between 45.45 and 50 percent coverage while private credit bureaus should have at least 26.25 percent coverage.
Keywords: G20; G29; L96; O40; O55; 330; Information sharing; Banking; Africa